A Philosophy of the Verb:: Bertram Brooker’s Early Canadian Mystical-Modernist Verse - Betts, Gregory (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Despite the recent surge in scholarship on early Canadian modernist poetry from between the wars, Bertram Brooker has been among a number of overlooked poets, partly because his interest in mysticism sets him apart from the more prevalent modes of modernism. Brooker's poetry, written in the 1920s and early 1930s but collected for the first time in Birk Sproxton's 1988 edition, Sound Assembling, demonstrates his view of verbs (as representations of spiritual participation in reality) in an otherwise limiting system of language and his belief that all living things are linked in a way that transcends individuality. The mystical elements of his poetry reveal the alienation of the modern individual from the cosmos; however, Brooker remains focused on cosmic unity rather than revelling in fragmentation with contemporaries such as T.S. Eliot and Ezra Pound. Through his art and poetics, he seeks a solution to the perceived problem rather than simply embracing it.